Characterization of the direct targets of FOXO transcription factors throughout evolution. Issue 4 (8th April 2016) - Webb, Ashley E.; Kundaje, Anshul; Brunet, Anne
Summary: FOXO transcription factors (FOXOs) are central regulators of lifespan across species, yet they also have cell‐specific functions, including adult stem cell homeostasis and immune function. Direct targets of FOXOs have been identified genome‐wide in several species and cell types. However, whether FOXO targets are specific to cell types and species or conserved across cell types and throughout evolution remains uncharacterized. Here, we perform a meta‐analysis of direct FOXO targets across tissues and organisms, using data from mammals as well as Caenorhabditis elegans and Drosophila . We show that FOXOs bind cell type‐specific targets, which have functions related to that particular cell. Interestingly, FOXOs also share targets across different tissues in mammals, and the function and even the identity of these shared mammalian targets are conserved in invertebrates. Evolutionarily conserved targets show enrichment for growth factor signaling, metabolism, stress resistance, and proteostasis, suggesting an ancestral, conserved role in the regulation of these processes. We also identify candidate cofactors at conserved FOXO targets that change in expression with age, including CREB and ETS family factors. This meta‐analysis provides insight into the evolution of the FOXO network and highlights downstream genes and cofactors that may be particularly important for FOXO's conserved function in adult homeostasis and longevity.